The complete plastome sequences of five Aponogeton species (Aponogetonaceae): Insights into the structural organization and mutational hotspots - Virginia M. Mwanzia (Plant Diversity, 2020)
Members of the aquatic plant genus Aponogeton are widely used commercially in aquariums because of their variable leaf shape and unique inflorescences. However, due to extensive similarity between species in this genus, morphological characters are generally inadequate for taxonomic classification. Currently, molecular makers available for taxonomic and phylogenetic studies of Aponogeton are limited. One approach to clarifying relationships between species in these complex groups is to use divergence hotspot regions within the genome. Here, we sequenced and analyzed the plastomes of five Aponogeton species collected from China, Zambia, and Kenya, and subsequently screened these plastomes for divergent DNA hotspots. The five plastomes are circular structures with sizes ranging from 154,167 bp to 154,860 bp. The Large and the Small Single Copies are separated by two Inverted Repeats. One hundred and thirteen unique genes were identified including 79 protein-coding, 30 tRNA, and four rRNA genes. We found that the most abundant repeats in all but one species were mononucleotide repeats (A/T) and that there were 23 potential RNA ending sites. Interestingly, a ~3 kb inversion, which includes the accD gene, was detected within the Asian species of Aponogeton. The inversion may be related to more frequent exchanges between this region and the nuclear genome. Furthermore, we detected mutational hotspot sites among the five Aponogeton species. Three of these hotspots are intergenic spacer regions (accD-psaI, rbcL-accD and trnH-GUG-psbA) that might be suitable for use as barcodes to resolve intra-generic relationships. We also identified four highly variable protein-coding genes (ccsA, rpl22, rps16 and ycf1) may be used as barcodes to resolve the higher-level phylogenies. Our study will provide valuable molecular resources for the taxonomic and phylogenomic study of the complex genus Aponogeton.